Insight into non‐enzymatic browning of shelf‐stable orange juice during storage: A fractionation and kinetic approach. (3rd May 2020) - Pham, Huong Tran Thuy; Bista, Archana; Kebede, Biniam; Buvé, Carolien; Hendrickx, Marc; Van Loey, Ann
Abstract: BACKGROUND: Non‐enzymatic browning (NEB) is the main quality defect in shelf‐stable orange juice and other fruit juices during storage. Previous studies on NEB focused solely on the soluble fraction of orange juice, regardless of the fact that both soluble and insoluble fractions turn brown during extended storage. Clear evidence of the relative contribution of both fractions to NEB is currently lacking in the literature. This study investigated the contribution of the soluble and insoluble fractions of orange juice, which were obtained by centrifugation and ethanol precipitation, to NEB during storage. Changes in different NEB‐related attributes, such as ascorbic acid (AA) degradation, and the browning index (BI), were quantified and kinetically modeled. RESULTS: Evaluation of color during storage showed that the orange juice and the soluble compound‐containing fractions turned brown whereas the insoluble fractions did not. The soluble compound‐containing fractions showed exactly the same browning behavior with storage as the plain orange juice. Based on the kinetic parameters obtained, the degradation of AA, the hydrolysis of sucrose, the increase in the glucose and fructose content, and the formation of furfural and 5‐hydroxymethylfurfural during storage were similar for the plain orange juice and the soluble compound‐containing fractions. CONCLUSION: This work provided evidence that the soluble fraction of orange juice plays the major role in NEB, unlike the insoluble fraction, which seems to make no contribution. Results from this work also demonstrate the potential use of the soluble fraction as an orange‐juice‐based model system of reduced complexity that can be used for the further investigation of NEB processes. © 2020 Society of Chemical Industry